2019
DOI: 10.1038/s41598-019-41762-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the energy recovery potential of waste Photovoltaic (PV) modules

Abstract: Global exponential increase in levels of Photovoltaic (PV) module waste is an increasing concern. The purpose of this study is to investigate if there is energy value in the polymers contained within first-generation crystalline silicon (c-Si) PV modules to help contribute positively to recycling rates and the circular economy. One such thermochemical conversion method that appeals to this application is pyrolysis. As c-Si PV modules are made up of glass, metal, semiconductor and polymer layers; pyrolysis has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…The authors observed that the main pyrolysis reactions occurred between 400°C and 500°C and that temperature increases beyond the upper bound did not produce a significant mass loss. Farrell et al (2019) looked at the effect of pyrolysis on EVA backsheet and two-stage decomposition was observed. In the first stage in which a temperature range was from 310 to 390°C, there was the removal of acetic acid from the vinyl acetate monomer within the EVA structure, with a mass loss of approximately 22.6 wt.%.…”
Section: Pv Modules Recycling Methodsmentioning
confidence: 99%
“…The authors observed that the main pyrolysis reactions occurred between 400°C and 500°C and that temperature increases beyond the upper bound did not produce a significant mass loss. Farrell et al (2019) looked at the effect of pyrolysis on EVA backsheet and two-stage decomposition was observed. In the first stage in which a temperature range was from 310 to 390°C, there was the removal of acetic acid from the vinyl acetate monomer within the EVA structure, with a mass loss of approximately 22.6 wt.%.…”
Section: Pv Modules Recycling Methodsmentioning
confidence: 99%
“…In other countries, tackling PV modules waste are also proved to be valuable from energy, environment, and economic perspectives (Farrell et al, 2019;Gönen & Kaplano glu, 2019) and management of the end-of-life PV components has already started in some countries and regions where the industry chain is developed and mature. Japan is, for example, the first country that conducted researches on PV recycling technologies as early as 2000.…”
Section: Process Of Pv Modules End-of-life Management and Global Stmentioning
confidence: 99%
“…Biomass, unlike other sustainable energy sources such as wind, solar, geothermal, marine and hydropower, can directly produce fuel along with chemicals (Quereshi et al 2021;Farrell et al 2019;Farrell et al 2020). Thus, it is not feasible to substitute fossil-based fuels with the aforementioned sustainable energy sources; hence, biomass utilisation to produce fuel and chemicals is required (Bharti et al 2021).…”
Section: Introductionmentioning
confidence: 99%